RANCANG BANGUN SISTEM KONTROL KECEPATAN MOTOR MENGGUNAKAN SENSOR SUHU LM 35 - Sonny Rumalutur (LPPM Poltek ST Paul, 2018)
This research is about controlling the circulation of room temperature which is done automatically if the room temperature is cold then motor rotation speed so slowly and vice versa if the room temperature is hot then motor rotation speed will be faster. In this study controlling the circulation of the room temperature with the fan in the activation is made automatically that is equipped with LM 35 temperature sensor which is then controlled using Arduino Uno and can adjust the speed of rotation from the fan. The fan can work automatically so it can simplify the man who previously the fan activation process is done by humans. And also can be more efficient in energy consumption because the fan works at the necessary time only. From the test results obtained that the system can work well in accordance with the planning and the role of the sensor is very important that can affect the overall success rate that is after the adjustment between software and hardware is equal to 80% by conducting tests periodically.